2011
DOI: 10.1249/mss.0b013e3181fca1ea
|View full text |Cite
|
Sign up to set email alerts
|

Are Women with Fibromyalgia Less Physically Active than Healthy Women?

Abstract: Purpose The primary purpose was to quantify and compare physical activity in fibromyalgia (FM) patients to age-matched healthy controls using both objective and self-report measures. Secondary purposes were to compare self-reported and objective measurement of physical activity and to evaluate the relationship between physical activity and pain and mood. Method Patients with FM (n = 39) and healthy controls (n = 40) completed the International Physical Activity Questionnaire and wore an accelerometer at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
142
1
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(166 citation statements)
references
References 33 publications
14
142
1
9
Order By: Relevance
“…A recomendação existente é utilizá-lo ao nível da cintura 29 , porém em pacientes adultos com fibromialgia apenas um estudo, e recente 30 , se propôs a tal finalidade. Isto é um indicativo de quanto limitado é caracterizar a associação do NAF com a dor.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A recomendação existente é utilizá-lo ao nível da cintura 29 , porém em pacientes adultos com fibromialgia apenas um estudo, e recente 30 , se propôs a tal finalidade. Isto é um indicativo de quanto limitado é caracterizar a associação do NAF com a dor.…”
Section: Discussionunclassified
“…Isto é um indicativo de quanto limitado é caracterizar a associação do NAF com a dor. Os próprios autores do estudo, citado acima 30 , assumem que não há relação entre essas duas variáveis. Futuras pesquisas podem investigar melhor a relação entre nível de atividade física, dor e capacidade funcional.…”
Section: Discussionunclassified
“…187 Weak correlations between self-reported and objectively measured physical activity have also been observed elsewhere. 128 It is likely that the self-reported and accelerometer data are measuring different dimensions of physical activity (e.g., perceived…”
Section: Performance-based Measuresmentioning
confidence: 99%
“…In the abovementioned two studies, the physical activity was measured using an accelerometer. McLoughlin et al 27 compared levels of physical activity between the FMS patients and healthy controls using both objective and self-report measures and demonstrated that physically activity levels were lower in the FMS patients. They indicated that physical activity levels were associated with depressed mood rather than being predictive of pain.…”
Section: Discussionmentioning
confidence: 99%